Introduction: The intermittency of youth migration - Cairns, D.; Clemente, M. (The Palgrave handbook of youth mobility and educational migration, 2021)
This book presents different perspectives on youth migration, focusing upon research from a wide range of geographical contexts. While diverse, what theoretically unites the assembled chapters is the idea that migration as practised by young people has fragmented into disparate episodes. Rather than becoming migrants in the classical sense of following a path with a clear beginning, middle and end, young people tend to move intermittently, in a more circular manner and for different, frequently overlapping reasons such as education, work and training. They may not even see themselves as migrants—especially in the very early stages of a spatial trajectory—but when we take into account the accumulation of mobility experiences being consumed, starting with what may be relatively short duration stays abroad, we come to see that they are actually practising migration, albeit in a manner different to established ideas that centre on the idea of settlement. Another way of looking at this situation would be to see moves abroad during the youth phase as precursors to longer duration stays later in life. What happens at a young age hence comes to matter a great deal to professional development, as this can be the time of life when the knowledge and skills required to become a migrant are generated, along with an awareness of how to make effective decisions about where and when to go.